Ciclo Biológico de la Mosca de la Fruta del Género (anastrepha spp.) a dos temperaturas, Salache – Cotopaxi 2020. - Reimundo Topón, Luis Miguel (2020)
The research was carried out at the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, with geographic coordinates of 00º 59 ’57’’ South latitude and 78º 37’ 14’’ West longitude. To observe the biological cycle of (Anastrepha spp.) at two temperatures (20 - 25 ° C). The methodology consisted of observing the development of (Anastrepha spp.) at two controlled temperatures, having as host, guava the samples were randomly collected from mature fruits found in the soil geographically referenced (GPS points, temperature, altitude, humidity). Subsequently, the samples were transported to the entomology laboratory for their respective breeding in the growth chambers with the controlled conditions of temperature and feed for the development of flies. Therefore, the research had a daily evaluation based on data collection, observation of each stage, without forgetting food and temperature review, which was constant at 20 ° C and 25 ° C.As results, two life tables at 20 ° C and 25 ° C were obtained, using the alphabetical keys of the Insect Life Cycle Modeling (ILCYM) software developed by the International Potato Center (CIP), which allow design a model of each biological stage of insects. From the results it can be said that the egg stage took 5 days for the two temperatures 20 ° C and 25 ° C respectively. For larval phase, it took 28 days at 20 ° C and 21 days at 25 ° C. On the other hand, the pupa stage took 29 days at 20 ° C and 25 days at 25 ° C. Finally, the adult stage took 55 days for 20 ° C and 29 days for 25 ° C. It is concluded, that at low temperatures the days of life are prolonged from the larval stage. This is because flies do not accumulate the heat necessary for the formation and maturation of reproductive organs, the process becomes slower generating longevity in (Anastrepha spp.). At 25 ºC, ovarian maturation is faster and mean longevity is shorter.